A Pragmatic Analysis of Rapport Orientation in Selected Rehabilitated Schools in Syria - Ahmad Abdulkareem Shaban; Rana M. Mowafak Dakhel; Samar Habeeb Ali; Maurice Elie Moarbes (International Journal of Education Sciences, 2024)
Rapport orientations are not frequently explored in educational discourse, despite their significant role in enhancing or maintaining relationships between students and teachers, and in avoiding or mitigating embarrassing situations. This paper aims to investigate the rapport orientations of students and teachers based on Spencer-Oatey’s (2008) theory. A descriptive-analytical method was adopted to analyze and interpret the questionnaires from students and teachers in selected rehabilitated schools in Syria. The software MAXQDA was used to comprehensively analyze the data. The results showed that most students had a tendency to be focused on improving their teachers' viewpoints. The results also show that teachers’ orientations in students’ perspectives tend to be enhancement-focused, although around half of the students do not mind whether their teachers’ rapport orientation is enhancement or neglect/challenge. It is worth noting that some teachers do not prioritize building rapport with their students or are oriented toward neglect or challenge rapport, according to students’ perspectives. Factors such as students’ motivation and satisfaction, personality, and teachers’ awareness of teaching methods are all considered in this study to provide a comprehensive analysis of the phenomenon.
Keywords: Rapport orientation; educational discourse; motivation; rehabilitated schools; student-teacher relationship